Harmonisasi Hukum Investasi Dan Hukum Dagang Di Negara-Negara Asean (Lex Jurnalica, 2006)
Regional  integration , especially  the economic side has proved  to be a kind of  vital passport to economic development. Several opinions and  theories  have been put forward  by  exponents of  this highly  controversial  issue  to be  selected by states actors appropriate to their national goals. At  present there is a general awareness  that economic  cooperation requires the development of a harmonious relationship between  economic and  political policies both  at the national  and  multinational level. What  should  be emphasized is that  in  order  to   encourage  economic  cooperation  among  the ASEAN countries  as  a means of  enhancing the rate of economic development, there  should be a radical changed  in  the role of  politics to ensure that it contribute positively to  economic cooperation. Mindful of  the economic,sosial, political and legal  fragmentation prevail in the ASEAN  countries,  the harmonization of  investment  and  trade laws is a  prerequisite to  economic  integration  for  the  regional  cooperation  in  Southeast  Asia  in  the  future.Keywords: Harmonization, law,  Asean country